IDENTIFIKASI BAKTERI Escherichia coli PADA MINUMAN TEH KEMASAN INDUSTRI RUMAH TANGGA DI KELURAHAN SUNGAI DAMA DAN SELILI MENGGUNAKAN METODE MOST PROBABLE NUMBER (MPN) - Fitri Handayani; Reksi Sundu; Dawia Dawia (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Tea beverage packaging is a popular fast food beverage because it has a variety of flavors that are in great demand by the public. Presentation of packaged tea beverages is mostly found in roads that may be contaminated by Escherichia coli bacteria. This study aims to identify Escherichia coli bacteria in packaged tea drinks circulating in the rivers of Kelurahan Selili. This research is a descriptive research. The sample used is packaged tea drink taken in two subdistricts of Samarinda ilir namely Selili urban village and Sungai Dama by using Purposive Sampling method of 10 samples. Sample tests include presumtive test, confirmative test and completed test. The LB (Lactose Broth) assay test was used to detect early presence of Coliform bacteria, BGLBB (Brillian Green Lactose Bile Broth) as a detector of the specification of the presence of Coliform bacteria and completed test using EMBA (Eosin Methylene Blue Agar) as Escherichia coli. The results of this study were 7 samples of 10 samples tested containing Escherichia coli.